EXTROVERT PERSONALITY AND ITS IMPACT ON STUDENTS’ ARGUMENTATIVE ESSAY WRITING SKILL - Wida Sopia Marwa; Nani Ronsani Thamrin (University of Kuningan, 2016)
This research aims at finding the positive correlation between extroversion personality and students’ argumentative essay writing skill. The objective of this research is to know the correlation between extroversion personality and students’ argumentative essay of sophomore English Department students in University of Kuningan. The population in this research was all sophomore English Department students with total 60 students. A convenience purposive sampling was applied to get the sample students. The samples of this research were 12 extrovert students. From the results of statistical tests to test the correlation between two variables, this research used Pearson product moment. As the result of the calculation, it was found that robserved (0,778) ttables (0, 532). Then, based on the hypothesis test with two tail test, the result of hypothesis test obtained tobserved (3, 917) ttables (1, 782). Thus, it can be concluded that Ha was accepted and there was a correlation between extroversion personality and students’ argumentative essay writing skill.Keywords: extroversion personality, argumentative essay, writing, Eysenk personality inventory